The International Finance Corporation’s Engagement in Fragile and Conflict-Affected Situations : Results and Lessons - Independent Evaluation Group (World Bank, Washington, DC, 2019)
Fragility, conflict and violence (FCV) pose a major challenge for development and for reaching the Bank Group’s twin goals. Enabling appropriate private sector activities can be a means to break free of the fragility trap by supporting economic growth, promoting local employment and income earning opportunities, generating government revenues, and delivering goods and services. However, the private sector faces substantial constraints in fragile and conflict-affected situations (FCS). This report takes stock of available evidence regarding the effectiveness of IFC’s support in FCS. It aims to inform IFC’s strategy in FCS as IFC seeks to scale up its activities in FCS as part of its commitments under the Capital Increase Package, and to provide inputs for the Bank Group’s Fragility, Conflict and Violence (FCV) strategy currently being developed.